Intrepid Teacher Abroad: Advancing Teacher Knowledge and Professional Achievement through A Short Term, International, Early Field Experience Teaching Place-Based Art in Japan - Cotner, Teresa (International Journal for Innovation Education and Research, 2019)
This study describes development of teacher knowledge through a short term, early field experience, for preservice teachers who taught place-based art lessons in a community-center in Japan. Eight U.S. undergraduate, pre-credential students participated in this study. The author of this paper, a participant observer, collected and examined pre- and post-questionnaire responses, participant observation field notes, photographs, and one three-years-after reflection, through constant comparison, thematic analysis, and explanatory case study.  This study found no negative outcomes for preservice teachers. Findings from this study concur with a growing body of literature that explores how a short term, international, early field experience can foster the development of teacher knowledge, including pedagogy, subject matter, students and environmental context, and further suggest that short term, international, early field experiences teaching place-based art can foster professional achievement.